2021
DOI: 10.17576/jsm-2021-5008-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Antioxidant and α-Glucosidase Inhibitory Activity of Collagen Hydrolysate from Lamuru (Caranx ignobilis) Fishbone

Abstract: The Lamuru fish (Caranx ignobilis) is mostly found in tropical waters of the indo-pacific region, namely Indonesia. It is believed to contain collagen and this study aims to isolate collagen from its bone and determine the collagen’s antioxidant and α-glucosidase inhibitory activity. In our study, the collagen was extracted using acetic acid which was hydrolyzed by collagenase enzyme from Clostridium histolyticum at a temperature of 37 °C, and pH 7.0. During hydrolysis, the degree of hydrolysis (DH) was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The antioxidant activity of plant extracts in the FRAP assay is based on a linear regression equation from the standard FeSO4 curve. 28 The result revealed that Ethyl acetate extract exhibited a higher FeEAC value than the methanol and hexane extracts. However, when compared with ascorbic acid, the FeEAC value of the ethyl acetate extract was much lower.…”
Section: Antioxidant Activity Testmentioning
confidence: 93%
“…The antioxidant activity of plant extracts in the FRAP assay is based on a linear regression equation from the standard FeSO4 curve. 28 The result revealed that Ethyl acetate extract exhibited a higher FeEAC value than the methanol and hexane extracts. However, when compared with ascorbic acid, the FeEAC value of the ethyl acetate extract was much lower.…”
Section: Antioxidant Activity Testmentioning
confidence: 93%
“…More p-nitrophenol is formed when the yellow color of the solution is more intense. 41 Testing the inhibition of α-glucosidase enzyme activity by the positive control (acarbose) aims to validite and ensure the reliability of the test. Acarbose is a pseudo-tetrasaccharide with a structure similar to an oligosaccharide, with a nitrogen atom present between the first and second glucose molecules, this increases the affinity of acarbose for α-glucosidase enzyme.…”
Section: Anti-diabetic Activity Of Diospyros Malabarica Extract Alpha...mentioning
confidence: 99%
“…Several marine species such as mussels, fish, and algae are sources of antioxidant peptides produced by enzymatic hydrolysis [104]. Collagen peptides with antioxidant activity have been developed from a variety of fish processing by-products, such as grass carp scales [14], squid (Dosidicus gigas) by-products [105], salmon scales [106], hammerhead shark skin [107], redlip croaker (Pseudosciaena polyactis) scales [50], skipjack tuna (Katsuwonus pelamis) [108], and lamuru (Caranx ignobilis) fishbone [109]. The two most common assays for antioxidant activity of peptides are the scavenging of DPPH radicals and the scavenging of ABTS radicals [72].…”
Section: Antioxidant Activitymentioning
confidence: 99%